2001
DOI: 10.1164/ajrccm.164.9.2103032
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil as Adjunct Therapy for Daytime Sleepiness in Obstructive Sleep Apnea

Abstract: Patients with obstructive sleep apnea/hypopnea syndrome can experience residual daytime sleepiness despite regular use of nasal continuous positive airway pressure therapy. This randomized, double-blind, placebo-controlled, parallel group study assessed the efficacy and safety of modafinil for the treatment of residual daytime sleepiness in such patients. Patients received modafinil (n = 77) (200 mg/d, Week 1; 400 mg/d, Weeks 2 to 4) or matching placebo (n = 80) once daily for 4 wk. Modafinil significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(174 citation statements)
references
References 60 publications
5
160
1
8
Order By: Relevance
“…In the latter study it was suggested that a sleep-deprivation protocol would be necessary to observe alertness-enhancing effects in healthy volunteers, because modafinil at a dosage of 200 mg has been effective in promoting alertness when healthy volunteers were sleepdeprived (Wesensten et al, 2002;Walsh et al, 2004). It has also been found to be alerting in patients with reduced baseline alertness levels (US Modafinil in Narcolepsy Multicentre Study Group, 1998Group, , 2000Pack et al, 2001;Rammohan et al, 2002;Szabadi et al, 2002;Rosenthal and Bryant, 2004). However, the present study has demonstrated that the larger dose of 400 mg is sufficient for the observation of an alerting effect in a small group of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study it was suggested that a sleep-deprivation protocol would be necessary to observe alertness-enhancing effects in healthy volunteers, because modafinil at a dosage of 200 mg has been effective in promoting alertness when healthy volunteers were sleepdeprived (Wesensten et al, 2002;Walsh et al, 2004). It has also been found to be alerting in patients with reduced baseline alertness levels (US Modafinil in Narcolepsy Multicentre Study Group, 1998Group, , 2000Pack et al, 2001;Rammohan et al, 2002;Szabadi et al, 2002;Rosenthal and Bryant, 2004). However, the present study has demonstrated that the larger dose of 400 mg is sufficient for the observation of an alerting effect in a small group of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80] Modafinil and armodafinil are generally well tolerated in patients with OSA. [81][82][83][84] It is important to note, however, that neither modafinil nor armodafinil addresses the underlying obstruction that causes OSA and must be used in conjunction with CPAP to avoid the return of symptoms and cardiovascular complications. Patients should be counseled to ensure compliance with CPAP when using adjunctive pharmacotherapy.…”
Section: Evaluation and Treatment Of Residual Esmentioning
confidence: 99%
“…Due to lack of controlled trials with long term follow up, modafinil is currently not recommended in untreated patients with OSA. 43,44 Oxygen is sometimes used in patients with central apnea caused by heart failure. It is not used to treat obstructive sleep apnea.…”
Section: Pharmacological Therapy:-mentioning
confidence: 99%